Construction and field tests of jointed reinforced concrete pavement made of sea sand concrete and GFRP reinforcement - Xi Wu; Liang Huang; Hao Yang; Shuisheng Li (Case Studies in Construction Materials)
The utilization of sea-sand concrete (SSC) reinforced with glass fiber reinforced polymer (GFRP) bars presents a viable solution to address both the scarcity of river sand resources and the corrosion susceptibility of conventional steel reinforcement in marine environments. This study presents a field case study of a stretch of jointed reinforced concrete pavement (JRCP) fabricated with GFRP bars and SSC in a port infrastructure project. Mechanical performance of the GFRP-SSC pavement system was investigated through early-age time-dependent behavior observations, vehicle load tests, and numerical analysis. Early-age analysis of the tested pavement section indicated that SSC exhibited greater expansion than river sand concrete (RSC) within the first 5 h after pouring. Additionally, an increased reinforcement ratio of GFRP bars was observed to mitigate concrete shrinkage. The results of vehicle load tests and numerical analysis demonstrate that the GFRP bars maintain relatively low stress level under the design vehicle load, and the stress induced by a single vehicle load is insufficient to cause cracking or failure of the GFRP-reinforced pavement. Then, the effects of design parameters, including the arrangement of GFRP bars, the thickness of the pavement slab, and the elastic modulus of the base layer, on the structural behavior of GFRP-SSC pavement were analyzed through a parametric study. Over all, the case study demonstrates that the GFRP-SSC pavement exhibits comparable working performance to steel reinforced RSC pavement, making it a viable alternative for construction of JRCP engineering in coastal and island regions.